THE INFLUENCES OF MODERNITY TO KWEI-LAN AND THE HUSBAND IN PEARL S. BUCK’S EAST WIND: WEST WIND - UMMUL KHOIRIYAH (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2015)
Abstrak Studi ini berkaitan dengan perbedaan antara Barat dan Timur melalui tradisi dan modernitas kedua tokoh utama dalam novel Pearl S. Buck berjudul East Wind: West Wind. Tradisi digambarkan oleh Kwei-Lan, wanita China yang terkejut saat dituntut untuk beradaptasi dengan cara hidup suaminya yang berbeda setelah tinggal di Barat bertahun-tahun. Modernitas menjadi krusial terhadap perilaku dan pemikiran Kwei-Lan yang konservatif. Masalah dimulai saat Kwei-Lan beranggapan bahwa dampak mimicry terhadap kultur Barat suaminya menjadi ancaman terhadap karakternya. Dengan rasionalitas dan intelegensi yang dimiliki suaminya, pada akhirnya Kwei-Lan mengikuti cara baru suaminya. Pertanyaan, keraguan, dan kebingungan merupakan simbol ambivalensi yang Kwei-Lan alami melalui modernitas suaminya. Studi ini mengungkap tradisi China Kwei-Lan dan modernitas Barat suaminya menggunakan teori post colonial dari Homi Bhabha. Studi ini menggunakan teori tersebut, sebab Si Suami menunjukkan performa sebagai colonizer dan mengimitasi cara Barat ketika itu berhubungan dengan kebebasan. Si suami menunjukkan cara baru untuk melindungi karakter Kwei-Lan dari tradisi patriarki yang membatasi kebanyakan wanita China. Analisis studi ini menunjukkan pengaruh modernitas terhadap kedua tokoh: adanya adopsi dan adaptasi terhadap budaya Barat dan pencampuran kultur China dan Barat. Secara keseluruhan, analisis membuktikan teori Homi Bhabha mengenai korelasi dan koeksistensi Barat dan Timur yang muncul dalam novel. Penginterpretasian modernitas mengenali kesalahan konsep kemanusiaan dan mengurai perubahan baru yang signifikan yang lebih baik mengenai detail kehidupan. Kata kunci: Tradisi, modernitas, post kolonialisme. Abstract This study deals with a condition of contrastion between tradition and modernity of two major characters in Pearl S. Buck’s East Wind: West Wind. The tradition is presented well by Kwei-Lan, an ordinary Chinese woman who is startled to be adapted with the opposite way of life of her Chinese husband who has come from Western country after years. The matter of modernity becomes crucial to the extent of Kwei-Lan’s conservative conduct and thought. The problem occurs when Kwei-Lan assumes her husband’s effect of mimicry towards Western culture as a threat to her character since the beginning. With rational and intellegent senses her husband has, Kwei-Lan finally taken in the new way of him. Question, hesitant, and confusion become common signs of ambivalence Kwei-Lan experiences throughout her husband’s modernity. This study reveals Kwei-Lan’s Chinese tradition and her husband’s Western modernity using post colonial theory of Homi Bhabha. This study uses it so since the husband shows the performance of colonizer and somehow imitates Western ways as it comes with the notion of freedom. The husband shows a new way of protecting Kwei-Lan’s character from tradition of patriarchy that restraints most of Chinese women. The analysis of this study will possibly mark the influences of modernity to both characters briefly: the emergence of adoption and adaptation of Western culture and the mixture of Chinese and Western culture. Overall, the analysis verifies and convinces the theory of Homi Bhabha about the correlation and co-existence of East and West appear in the novel. The interpretation of modernity recognizes the fallacy of humanity concept and sets new significant changes that are apart better in detail of manner of living. Keywords: Tradition, modernity, post colonialism.